2008
DOI: 10.1007/s10295-008-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-phase partitioning of α-galactosidase from fermented media of Aspergillus oryzae and comparison with conventional purification techniques

Abstract: Simple, attractive and versatile technique, three-phase partitioning (TPP) was used to purify alpha-galactosidase from fermented media of Aspergillus oryzae. The various conditions required for attaining efficient purification of the alpha-galactosidase fractions were optimized. The addition of n-butanol, t-butanol, and isopropanol in the presence of ammonium sulfate pushes the protein out of the solution to form an interfacial precipitate layer between the lower aqueous and upper organic layers. The single st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 21 publications
(24 reference statements)
0
22
0
2
Order By: Relevance
“…They were also unscalable, time consuming, expensive multistep protocols [2][3][4][5][9][10][11][12]. Three phase partitioning has relatively recent use for bioseperation of enzymes and inhibitors [13][14][15][16][17]. It uses ammonium sulfate with certain saturation to precipitate the protein and tbutanol is added to make three phase layers and to remove lipids, phenolic compounds and some detergents [13,18].…”
Section: Optimization Of Tpp Conditionsmentioning
confidence: 99%
“…They were also unscalable, time consuming, expensive multistep protocols [2][3][4][5][9][10][11][12]. Three phase partitioning has relatively recent use for bioseperation of enzymes and inhibitors [13][14][15][16][17]. It uses ammonium sulfate with certain saturation to precipitate the protein and tbutanol is added to make three phase layers and to remove lipids, phenolic compounds and some detergents [13,18].…”
Section: Optimization Of Tpp Conditionsmentioning
confidence: 99%
“…preferencyjne gromadzenie się laktoferyny w fazach dolnych, podczas gdy pozostałe białka, po wysoleniu w tych warunkach, były obecne w fazach środkowych. Podobną zależność zaobserwowali Dhananjay i Mulimani [9] podczas ekstrakcji α-galaktozydazy w układach trójfazowych. Wpływ pH serwatki na stopień oczyszczenia i wydajność odzysku laktoferyny przedstawiono na rys.…”
Section: Wyniki I Dyskusjaunclassified
“…From the previous works showed that ammonium sulfate were superior to other salts [4], [9], [11], [14] and [15]. This might be due to the Hofmeister series, which is a classification of ions based on their salting-out ability [31] and [32].…”
Section: Effect Of Salts On Proteases Partitioningmentioning
confidence: 99%
“…Dhananjay et al [4] found that the optimum TPP condition for α-galactosidase was the use of 30% ammonium sulfate along with 1: 1 ratio of t-butanol to aqueous crude extract provided the recovery around 99%. From the previous works showed that ammonium sulfate were superior to other salts [4], [9], [11], [14] and [15].…”
Section: Effect Of Salts On Proteases Partitioningmentioning
confidence: 99%
See 1 more Smart Citation